Emerging thermal-responsive materials and integrated techniques targeting the energy-efficient smart window application - Ke, Yujie (2019)
Architectural windows that smartly regulate indoor solar radiation by changing their optical transmittance in response to thermostimuli are developed as a promising solution toward reducing the energy consumption of buildings. Recently, energy‐efficient smart window technology has attracted increasing scientific interest, with the exploration of energy‐efficient novel materials as well as integration with practical techniques to generate various desired multifunctionalities. This review systematically summarizes emerging thermoresponsive materials for smart window applications, including hydrogels, ionic liquids, perovskites, metamaterials, and liquid crystals. These are compared with vanadium dioxide (VO2), a conventional and extensively studied material for thermochromic smart window applications. In addition, recent progress on cutting‐edge integrated techniques for smart windows is covered, including electrothermal techniques, self‐cleaning, wettability, and also integration with solar cells for bifunctional energy conservation and generation. Finally, opportunities and challenges relating to thermochromic smart windows and prospects for future development are discussed.